Labeling and Biological Evaluation of 99mTc-HYNIC-Trastuzumab as a Potential Radiopharmaceutical for In Vivo Evaluation of HER2 Expression in Breast Cancer - Calzada, Victoria; Garcia, Fernanda; Fernández, Marcelo; Porcal, Williams; Quinn, Thomas; Alonso, Omar; Gambini, Juan Pablo; Cabral, Pablo (World Journal of Nuclear Medicine, 2013)
The amplification of HER2 gene has been described in several tumor types, mainly breast cancer with a subsequent increase in HER2 protein expression. Trastuzumab is a humanized monoclonal antibody that recognizes selectively the HER2 extracellular domain. The objective of the present work was to standardize the conjugation of Trastuzumab with Succinimidyl-hydrazinonicotinamide (HYNIC) and labeling with 99mTc to obtain 99mTc-HYNIC-Trastuzumab for use as in vivo tracer of the HER2 expression in breast cancer. The labeling procedure involved derivatization of 0.067 µmol of Trastuzumab with 0.33 µmols of HYNIC in dimethyl sulfoxide (DMSO). The mixture was incubated for 30 min. A mixture of Tricine and SnCl2.2H2O was prepared by add a solution of 44.6 µmols Tricine in 0.05 mL HCl 2.0 M and a similar volume of another solution containing 44.3 µmols SnCl2.2H2O in 0.5 mL HCl 2.0 M. Then, 0.05 mL of this mixed was added to the conjugated with 296 MBq of 99mTcO-4. The final mixture was incubated at room temperature (18-25°C) for 30 min. Radiochemical purity of the labeled solution was studied by chromatography, to evaluate 99mTc-Tricine, 99mTcO2.H2O, and free 99mTcO4-. Radiochemical purity was also evaluated by HPLC. Stability studies were tested in solution at 4°C and lyophilized at 4°C. Biodistribution studies were performed in healthy CD-1 female mice at 2, 5, and 24 h (n = 3) and CD-1 female mice spontaneous breast adenocarcinoma (n = 3). Scintigraphic images of spontaneous breast adenocarcinoma in female CD-1 mice were acquired in a gamma camera at 2, 5, and 24 h post-injection. Labeling was easily performed with high yields (>90%) and radiopharmaceutical stability for 24 h post-labeling. Stability studies revealed that antibody derivative must be lyophilized for undamaged storage. Biodistribution studies and imaging revealed excellent uptake in the tumor. Based on the results it was concluded that 99mTc-HYNIC-Trastuzumab could be a promising radiopharmaceutical for in vivo diagnosis of the HER2 status in breast with impact on treatment planning.
Keywords: Breast cancer; hydrazinonicotinamide; scintigraphy; 99mTc-labeling; trastuzumab